2010
DOI: 10.1387/ijdb.092893pr
|View full text |Cite
|
Sign up to set email alerts
|

A Sox5 gene is expressed in the myogenic lineage during trout embryonic development

Abstract: Sox proteins form a family of transcription factors characterized by the presence of a DNA-binding domain called the high-mobility-group domain (HMG). The presence of a large number of potential Sox5 binding sites in the trout promoter of Pax7, a gene which has emerged as an important regulator of neural and somite development, prompted us to clone trout Sox5 and to examine its expression pattern in the developing trout embryo. Using whole mount in situ hybridisation, we show here that the Sox5 transcript is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
(30 reference statements)
1
11
0
1
Order By: Relevance
“…Sox5 and Sox11 transcripts were also up-regulated in laser-captured samples from the peripheral domain of the myotome. We have recently shown that Sox5 is expressed in myogenic cells from the dermomyotome-like epithelium notably at the level of the dorsal and ventral lips [26]. We report in this study a similar pattern of sox11 expression, indicating that these two genes are transcribed in dermomyotome-derived cells prior their differentiation.…”
Section: Discussionsupporting
confidence: 77%
“…Sox5 and Sox11 transcripts were also up-regulated in laser-captured samples from the peripheral domain of the myotome. We have recently shown that Sox5 is expressed in myogenic cells from the dermomyotome-like epithelium notably at the level of the dorsal and ventral lips [26]. We report in this study a similar pattern of sox11 expression, indicating that these two genes are transcribed in dermomyotome-derived cells prior their differentiation.…”
Section: Discussionsupporting
confidence: 77%
“…The MRFs act downstream of, or in parallel with, the paired domain and homeoboxcontaining transcription factors Pax 3 and Pax 7 (Fig. 2;Buckingham & Vincent 2009), with several Sox genes contributing to the control of muscle differentiation (Rescan & Ralliere 2010). The cells at the major horizontal septum retain a connection with the notochord and are recognized as muscle pioneer cells with a distinct programme of gene expression.…”
Section: Development Of Skeletal Musclementioning
confidence: 99%
“…Sex determining region Y-box protein 5 (SOX5) is a member of the SOX family, which was identified based on the conserved homology of the high-mobility group DNA-binding motif (7). It has been reported that SOX5 is involved in the regulation of embryonic development (8), and is associated with various cancer types, including prostate cancer (9), glioblastoma (10), hepatocellular carcinoma (11), osteosarcoma (12) and nasopharyngeal carcinoma (13). In 2014, Pei et al (14) reported that in breast cancer, SOX5 induces epithelial-mesenchymal transition (EMT) by transactivation of Twist1 expression.…”
Section: Introductionmentioning
confidence: 99%